Udział duchowieństwa śląskiego w życiu narodowym i politycznym II Rzeczypospolitej - Olszar, Henryk (Śląskie Studia Historyczno-Teologiczne, 1999)
In a difficult period of struggle for borders, uniting of the Polish lands and formation of the rebearing country the Silesian clergy fulfilled its role very well. The priests, who engaged on Polish side met with vexations and became victims of terror. The Silesian priests’ national and political activity was appreciated with their election to the Seym and Senate of the Republic of Poland, the Silesian Seym and Silesian Voivode’s Counsil in Katowice. The priests were looking also for suitable for them a political organisation. They wished, they worked for such an organisation which the best met the requirements of the Church. It was – according to them – the National Democracy or the Christian Democracy. The society noticed the clergy’s merits rendering for building the independence of Poland and consolidation of its existence. The distinguishing priests were conferred national awards and honorary citizenship of the Silesian cities.